Farmers' awareness and factors affecting adoption of rapid composting in Mekong Delta, Vietnam and Central Luzon, Philippines (2012)
A survey of 417 respondents and focus group discussions among selected farmers were conducted in four villages in Mekong Delta, Vietnam and Central Luzon, Philippines. Key informants interviews among representatives of current adoptors of rapid composting, local authorities, agricultural extension offices, cooperatives, farmers' associations, women's groups, and other related institutional organizations in the study sites were also done. The study aimed to: a) determine the current practices of rice straw uses of the farmers in the study sites; b) describe farmers' awareness and perception about using rice straw to produce rapid compost with Trichoderma; and c) determine the factors affecting the acceptance of farmers to do rapid composting.

Farmers in the survey areas have low awareness on the use of Trichoderma for rapid composting. The logit model showed that household income and perceptions about rapid composting were significant factors affecting the acceptability of using Trichoderma for rapid composting both in Mekong Delta and Central Luzon. Farm size was another significant factor in Central Luzon. To enhance farmers' adoption of rapid composting the following recommendations are forwarded: 1) capability building of farmers; 2) develop stable supply system of Trichoderma and other activators; and 3) conduct of on-farm trials with both farmers and researchers doing the experiment.
Keywords: Rice trade